2007
DOI: 10.1021/bm0700688
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Complex Coacervate Core Micelles with Lysozyme

Abstract: Encapsulation of enzymes by polymers is a promising method to influence their activity and stability. Here, we explore the use of complex coacervate core micelles for encapsulation of enzymes. The core of the micelles consists of negatively charged blocks of the diblock copolymer PAA42PAAm417 and the positively charged homopolymer PDMAEMA150. For encapsulation, part of the positively charged homopolymer was replaced by the positively charged globular protein lysozyme. We have studied the formation, structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 33 publications
7
121
1
Order By: Relevance
“…Besides co-micellization with DNA and RNA, other biopolymers, such as proteins, peptides, and enzymes, may also be encapsulated to preserve and/or promote stability and function, as was demonstrated for KALA, [88,140] lysozyme, [121,122,[141][142][143][144][145][146]150] trypsin, [148,149] myoglobin, [104] and BSA [62]. Circular dichroism (CD) experiments on lysozyme-containing C3Ms demonstrated that the secondary structure of free and C3M incorporated lysozyme is identical [144].…”
Section: Comicellization With Proteins Peptides and Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides co-micellization with DNA and RNA, other biopolymers, such as proteins, peptides, and enzymes, may also be encapsulated to preserve and/or promote stability and function, as was demonstrated for KALA, [88,140] lysozyme, [121,122,[141][142][143][144][145][146]150] trypsin, [148,149] myoglobin, [104] and BSA [62]. Circular dichroism (CD) experiments on lysozyme-containing C3Ms demonstrated that the secondary structure of free and C3M incorporated lysozyme is identical [144].…”
Section: Comicellization With Proteins Peptides and Enzymesmentioning
confidence: 99%
“…The critical ionic strength can be determined from the inclination point in a plot of the (initially decreasing) static light scattering intensity upon increasing ionic strength, due to a decrease in particle mass and aggregation number upon micellar dissociation until the critical ionic strength is reached and no more C3Ms can be observed [29,96,100,150]. Similarly, the critical pH for C3M formation in systems wherein at least one component is a weak polyelectrolyte, can be determined from a plot of the static light scattering intensity versus pH [100,252].…”
Section: Static Light Scattering (Sls)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, for the other ingredient(s) one has quite some freedom. Simple polyelectrolytes of varying length have been used, but also proteins (enzymes) [23], ionic surfactants [24], and inor- Fig. 9 Symmetry breaking in a micelle with a mixed corona, as modeled by means of selfconsistent field calculations [19] imposing a non-deformable spherical core.…”
Section: Hierarchical Self-assemblymentioning
confidence: 99%